Integration of Dengue Fever Prevention into School Learning: An Experimental Study-Interactive Media for Dengue Fever Prevention - Ratna Dian Kurniawati; Martini Martini; Nur Endah Wahyuningsih; Dwi Sutiningsih (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2025)
Introduction: The risk of contracting Dengue can affect anyone, including school students. This fact poses a threat because there is no specific program related to Dengue prevention in the school environment. This study aims to test the effectiveness of HyperText Markup Language 5 (HTML5) with Smart Apps Creator as an interactive medium for dengue prevention integrated into learning. Methods: This research is divided into testing and evaluation stages. The testing stage was conducted through a true experimental design with a Pre-test, Post-test, and Control Group. The evaluation stage was conducted through a quasi-experimental design with a pre-test, post-test, and one-group intervention method. The research population was 5th-grade students of public elementary schools. The sample for the testing stage was 35 students for both intervention and control, and the sample for the evaluation stage was 396 students. The research sample was selected using simple random sampling. The research was conducted for 8 weeks. Data were obtained from filling out questionnaires for pre-test, post-test I, and post-test II. Ethical approval was obtained from Bhakti Kencana University ethics committee (98/09.kepK/UBK/VII/2023). Results: There was a significant difference in motivation in the media test and evaluation before and after the intervention through HTML5-based interactive game media with a smart app creator, with a p-value of 0.000. The intervention significantly increased motivation with a p-value of 0.000 compared to the control group in the media test. Likewise, the evaluation results p-value of 0.000. Thus, the intervention was proven effective in increasing motivation. Another indicator of success was that during the 4 weeks of observation, the presence of larvae decreased significantly. Even in the 4th week, no larvae were found in all the containers. Conclusion: The Dengue Prevention through HTML5 Interactive Media with Smart Apps Creator is significantly effective as an intervention because it can significantly increase motivation